ЯКІСНІ ХАРАКТЕРИСТИКИ ОДНОФАЗНОГО МОСТОВОГО ВИПРЯМЛЯЧА З АКТИВНИМ НАВАНТАЖЕННЯМ ТА ЄМНІСНИМ ФІЛЬТРОМ У РАЗІ ЖИВЛЕННЯ ВІД ДЖЕРЕЛА СТРУМУ - Спірін, В.М.; Губаревич, В.М.; Маруня, Ю.В.; Салко, С.В. (Інститут електродинаміки НАН України, Київ, 2020)
The electromagnetic processes in a single-phase bridge rectifier with active load and a capacitive filter at power supply from a symmetric inductive-capacitive converter (ICC), made according to the scheme T1-LCL, are compared and its qualitative characteristics are compared with the Г1-LC scheme of ICC. The T1-LCL scheme has better electromagnetic compatibility (, THDі<3%), than the Г1-LC scheme, but it has higher specific capacitance of the capacitor. References 10, figures 5, table 1.